Kontribusi Usaha Gula Aren Terhadap Pendapatan Keluarga Di Dusun Kalatin Kelurahan Lowu Utara Kecamatan Ratahan Kabupaten Minahasa Tenggara - Wungkana, Jevan Andre; Manginsela, Elsje Pauline; Tarore, Melissa Lady Gisela (AGRI-SOSIOEKONOMI, 2023)
This research aims to determine the magnitude of the contribution of the palm sugar business to family income in Kalatin Hamlet, North Lowu Village, Ratahan District, Southeast Minahasa Regency. This research was carried out for three months from January 2023 to March 2023 in Kalatin Hamlet, Ratahan District, Southeast Minahasa Regency. The sampling method in this research was carried out deliberately (purposive sampling), where the number of palm sugar processors sampled was 3 out of 15 respondents. The data analysis used in this research is descriptive quantitative analysis to analyze data by presenting, managing, describing and interpreting research results with words and sentences to answer the research objectives. The research results show that the palm sugar business contributes 78.08% to family income. The contribution of the palm sugar business to family income in Kalatin Hamlet, North Lowu District, Ratahan District, Southeast Minahasa Regency is categorized as very large because the value is >50%. The average income of palm sugar processors is IDR 712,620 per week from the sale of an average of 30 pieces of palm sugar at a price of IDR 12,000 per piece and the wife's total income is IDR 200,000 per week. The total family income earned by palm sugar processors in Kalatin Hamlet, Ratahan District, Southeast Minahasa Regency amounts to IDR 912,620.